THE STRATEGY TO INCREASE ROBUSTA COFFEE PRODUCTION AT OGANKOMERING ULU REGENCY OF SOUTH SUMATRA PROVINCE - Ely Brand; Fifian Permata Sari; Yetty Oktarina (Bajang Institute, 2022)
This study examines the strategy to increase robusta coffee production in OganKomering Ulu Regency, South Sumatra Province. This study aims to analyze the strategy of increasing robusta coffee production in OganKomering Ulu Regency, South Sumatra Province. The study was located OganKomering Ulu Regency, South Sumatra Province. The time of the research is December 2021. The research method used is the survey method. Research respondents were 84 coffee farmers in OganKomering Ulu Regency, 10 agricultural extension workers, 10 coffee traders and 3 people from the Department of Agriculture. Data analysis used descriptive analysis techniques (describe and explain the development of robusta coffee production in the research area, SWOT analysis (Stength, Weakness, Opportunities, Threats). The results of this study found that First, the majority of coffee farmers are in productive age so that they can be motivated to increase production. coffee by growing coffee intensively Second, taking advantage of the still high demand for coffee to motivate farmers to increase production in OganKomering Ulu Regency Third, the obstacle to increasing coffee production in OganKomering Ulu Regency is that there is enough land available for coffee plants, but the effort Farming is not done well, including maintenance, plant rejuvenation, lack of capital and the lack of guidance from agricultural extension workers, especially the sub-sector, even though the local government is very supportive.